DIRECT KICKS IN BOXING - Izet Kahrović; Benin Murić; Oliver Radenković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
Hit directly, giving any impact maximum muscle strength is skill, and it is neces- sary to the exercise and learning to make it perfect. Training begins with oral statement, so that students get to know with the techni- que that works. After oral exposure, it is necessary to create a good notion on technology that is adopted. The best way for the creation of good notion is a good demonstration. In direct training kicks in the box, you need patience and gradualness and there- fore uses a large number of additional exercises. In their work with beginners, in the first class, individual elements of technology, and also direct blow, it is necessary to separate the parts and run them on multiple commands, to later come to the confluence in one command. Direct wounds, with left and right hand, can be run from the towns, on the head and body, from the movement, to step forward, step back and step aside, the remedy to the left and right side. Left direct is taking out from a running protrusion hands, but kick, which is a pro- duct of the system, ankle-knee-pelvis and shoulder forward horizontaly. Set at the time of stripes, body weight over the left leg. Right direct from the place, starting ekscentrical reflecsive impuls of a extensor muscle in ankle, knee and joint of a hip.This kind of a sud- den movement is running simultaneously with the rotation of the body around vertical (longitudinal) axis, with the transfer body weight on the left leg. Further movement to the hand which serves as a lever, which is transmitted through the power stroke